New developments in sum of squares optimization and SOSTOOLS - Prajna, S; Papachristodoulou, A; Seiler, P; Parrilo, P; acc (2004)
We describe the latest additions to SOSTOOLS, a freely available MATLAB toolbox for formulating and solving sum of squares programs. Among the many improvements, there are native polynomial objects, structure-exploiting techniques for sparse and structured polynomials, new customized functions, and support for alternative SDP solvers. We sketch some of the theory behind the new improvements, and illustrate the new commands using control-oriented examples.